Localized Biphasic Malignant Peritoneal Mesothelioma with Rhabdoid Features Involving the Liver: Case Report and Review of the Literature - Dalal Hassan; Saverio Ligato (Hindawi Limited, 2019)
Introduction. Localized malignant mesotheliomas, defined as sharply circumscribed tumors of the serosal membrane with the microscopic appearance of diffuse malignant mesothelioma, are rare tumors; their behavior and prognosis are uncertain. Intrahepatic mesotheliomas are postulated to arise from mesothelial cells of Glisson's capsule. Case Presentation. A 69-year-old female with no history of asbestos exposure presented with a one-month history of increasing abdominal pain associated with constitutional symptoms. Computerized Tomography (CT) scan of the abdomen and pelvis revealed a sizable soft tissue mass within the right paracolic gutter, abutting the inferior hepatic margin, the lateral abdominal wall, and descending colon. Ultrasound-guided biopsy of the mass suggested a poorly differentiated hepatocellular carcinoma. There was no disease elsewhere on PET scan. Surgical resection of the mass was performed. Pathological assessment suggested the tumor to be arising from the liver with invasion of the liver, abdominal wall musculature, and the adventitial surface of the ascending colon. A final diagnosis of localized biphasic malignant peritoneal mesothelioma with rhabdoid features was rendered based on morphology and the result of immunohistochemical studies. The abdominal wall margin was positive. The patient progressed over the course of 6 months despite receiving adjuvant chemotherapy and immunotherapy with metastases and a decline in performance status and was transitioned to hospice. Conclusion. Localized malignant peritoneal mesotheliomas are rare tumors that may present clinically as a liver mass and simulate primary hepatic or secondary tumors. Definitive diagnosis is obtained by surgical resection in most cases. The clinical outcome is variable with most cases having a poor outcome.